Communicating agriculture information through mass media: an effort for creating knowledgeable farmers - Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Shahkat Ali, Muhamad Sham; Ramli, Nor Salbila (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
In the era of globalization, mass media indeed is a significant tool for development. Agriculture is one of the sectors that is developed through the power that mass media has. Its power in disseminating agriculture information to the farmers is indispensable, but the main question now, does the Department of Agriculture (DOA) as one of the main agriculture agencies in Malaysia, wisely utilize all the mass media sources to disseminate the valuable agriculture information to the farmers and their officers? The research approach for this study was a qualitative case study. Data was gained through three Focus Group Discussions (FGD) among DOA officers and farmers. The findings were in descriptive analysis. Based on the results gained, farmers are more relying on agriculture information in the form of printed materials compared to television, radio and internet. DOA has produced 17 types of printed publications besides being the major sources for radio and television agriculture programs aired at Radio Television Malaysia and Selangor FM. DOA also is one of the major sources of agriculture newspaper insert of Utusan Malaysia. DOA has their own website which is www.doa.gov.my for the public and the Agris Geo Portal which is created specifically for their staff. Some of the printed publications not reach the grass root level, finance and delayed information received are among the problems faced by DOA in the process of producing and disseminating their publication. DOA has not yet establish specific evaluation process for their printed and electronic publications, but for their website, they have internal and external evaluation. It is suggested that DOA at district level also should be given some allocation to produce their own publications. DOA should encourage other daily newspapers such as Harian Metro, The Star, Sin Chew Jit Poh and Tamil Nesan to have their own agriculture newspapers insert. It is recommended that publications on agriculture should be doubled, the best way to make it is through cooperation between DOA and giant agriculture based companies. The farmers should be provided with the schedule of the date of DOA publications to be disseminated to the farmers, the air time of television and radio program and list of agriculture agencies websites.